1998
DOI: 10.1007/s002470050376
|View full text |Cite
|
Sign up to set email alerts
|

Preamputation MR imaging in meningococcemia and comparison to conventional arteriography

Abstract: Meningococcemia is a life-threatening infection which produces purpura fulminans and extremity gangrene in its most severe form. In patients with gangrene, amputation is usually necessary. The amputations frequently need revision as ischemic changes in the underlying soft tissues and bone are difficult to evaluate at the time of surgery. These ischemic changes often have non-vascular distributions and progress over time. We present two patients in whom MR imaging and MR angiography were performed prior to plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Even at this stage, the margins of tissue survivability can be difficult to delineate with precision. MRI, with or without concomitant angiography, can give the surgeons an approximate level of debridement or amputation [24]. During surgery, intraoperative muscle or bone biopsy can demonstrate viability of tissue.…”
Section: Progressive Managementmentioning
confidence: 99%
“…Even at this stage, the margins of tissue survivability can be difficult to delineate with precision. MRI, with or without concomitant angiography, can give the surgeons an approximate level of debridement or amputation [24]. During surgery, intraoperative muscle or bone biopsy can demonstrate viability of tissue.…”
Section: Progressive Managementmentioning
confidence: 99%
“…Harley et al 17 suggested a level of amputation proximal to the imaged level of viability on Doppler scanning should be selected but still had high revision rates. Hogan et al 18 described the use of time of flight MR angiography for preoperative planning in 2 cases with meningococcemia. Watson et al, 19 however, report that some areas of nonenhancing muscle on MRI (presumed necrotic) were viable at surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Afin d'aider à la prise de décision chirurgicale, la réalisation de biopsies pour déterminer la viabilité des tissus restants peut être effectuée [29]. Mais c'est surtout l'IRM qui permettrait, pour certaines équipes [32], de délimiter en préopératoire les zones nécrosées notamment musculaires et osseuses. Les informations obtenues par cet examen les aideraient dans leur stratégie chirurgicale en diminuant le nombre d'interventions et en planifiant les gestes de reconstruction.…”
Section: Parage Et Amputationsunclassified